2008
DOI: 10.1038/clpt.2008.104
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Ritonavir Changes in Methadone Pharmacokinetics and Pharmacodynamics: I. Evidence Against CYP3A Mediation of Methadone Clearance

Abstract: Ritonavir diminishes methadone plasma concentrations, attributed to CYP3A induction, but actual mechanisms are unknown. We determined ritonavir effects on stereoselective methadone pharmacokinetics and clinical effects (pupillary miosis) in healthy HIV-negative volunteers. Subjects received intravenous plus oral (deuterium-labeled) racemic methadone after nothing, short-term (3 day) and steady-state ritonavir. Acute and steady-state ritonavir, respectively, caused 1.5- and 2-fold induction of systemic and appa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
119
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(128 citation statements)
references
References 53 publications
7
119
1
1
Order By: Relevance
“…Previous clinical studies also showed methadone bioavailability apparently unrelated to P-gp (or fexofenadine transporter) activity. Specifically, ritonavir, indinavir, ritonavir-indinavir, nelfinavir, and efavirenz, respectively, inhibited, inhibited, inhibited, induced, and induced fexofenadine efflux (suggesting altered P-gp activity), whereas methadone bioavailability was unchanged, unchanged, unchanged, decreased, and unchanged (Kharasch et al, 2008a(Kharasch et al, , 2009a(Kharasch et al, , b, 2012a. Together, these results do not suggest that intestinal P-gp significantly mediates methadone absorption and first-pass extraction, and thus transporter mechanisms of methadone bioavailability and drug interactions remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous clinical studies also showed methadone bioavailability apparently unrelated to P-gp (or fexofenadine transporter) activity. Specifically, ritonavir, indinavir, ritonavir-indinavir, nelfinavir, and efavirenz, respectively, inhibited, inhibited, inhibited, induced, and induced fexofenadine efflux (suggesting altered P-gp activity), whereas methadone bioavailability was unchanged, unchanged, unchanged, decreased, and unchanged (Kharasch et al, 2008a(Kharasch et al, , 2009a(Kharasch et al, , b, 2012a. Together, these results do not suggest that intestinal P-gp significantly mediates methadone absorption and first-pass extraction, and thus transporter mechanisms of methadone bioavailability and drug interactions remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…and oral methadone (Kharasch et al, 2004a(Kharasch et al, , 2008a(Kharasch et al, , 2009a(Kharasch et al, ,b, 2012a. Subjects received i.v.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In part, mishaps with methadone are a striking example that practitioners' basic understanding of opioid pharmacology is simply failing to keep up with the clinical applications of these drugs, a problem compounded by systematic deficiencies in overall knowledge acquisition and dissemination. 5,26 The most convincing metric of this failure is the mounting number of patient deaths. As identified by the Substance Abuse and Mental Health Services Administration, "Half of methadone deaths are pain patients who are being mismanaged by physicians who lack sufficient knowledge or skills to use methadone in the treatment of pain."…”
mentioning
confidence: 99%